How the Employee Engagement and Organizational Resilience affects Career Flexibility based on the Job Satisfaction of Henan Province：A Bibliometric Analysis Using the SPAR-4-SLR Approach - MI, WANG; Ali, Dhakir Abbas (Journal of Ecohumanism, 2024)
The growing demand for career path uncertainty in Henan Province, China, prompted by the post-COVID-19 "new normal," advancement in technology, and continuous economic growth, has brought about a significant disparity between theory and practice which further requires the attention of various scholars. This study seeks to determine how employee engagement and organizational resilience affect career flexibility, with job satisfaction as the mediating role. Furthermore, the study proposes the utilization of human capital theory to improve this intricacy and achieve a better effective career flexibility outcome. To achieve these objectives, the study sourced its data from the Scopus, utilizing Bibliometric Analysis, the SPAR-4-SLR protocol, and Microsoft Excel statistical tools for result analysis. The findings underline the significance of multidisciplinary methods in comprehending the intricate intersection between employee engagement, organizational resilience, job satisfaction, and career flexibility. The paper acknowledges the significant of the mammoth studies originated from China, where rapid economic and social transformations have brought to the fore new challenges and opportunities for the labor market. The study achieved that by utilizing the capability of human capital theory to determine the extent investments in employee development, skills, and knowledge can improve organizational performance and resilience. The mediating role of job satisfaction is critical, as it fosters an environment in which engaged and resilient employees can effectively manage changes in their career path. This method offers a meticulous plan for improving workforce flexibility in China and the world at large, by realigning with the changing goals of the modern workplaces. The study further recommends future research interest to broaden the study by incorporating emerging themes such as technology management and other variables such as leadership styles that can also be instrumental in the study.